High throughput sequencing-based analysis of microbial diversity in dental unit waterlines supports the importance of providing safe water for clinical use - Yuan Zhang; Yifan Ping; Ruyu Zhou; Juan Wang; Guangdong Zhang (Elsevier, 2018)
This study aims to explore the water quality of dental unit waterlines (DUWLs) and the diversity of microbial communities in DUWLs. Water samples from 33 dental chair units (DCUs) were collected, diluted and then spread on sterilized R2A plate for incubation. Subsequently, the microbial colony-forming units per milliliter (CFU/ml) were recorded by an automatic colony analyzer. Total DNA extracted from the rest of the samples was tested on the Illumina MiSeq PE300 platform. T-test and Kruskal-Wallis rank test were adopted for statistical analysis. Significance was assumed at a P < 0.05. After incubation, the average total microbial count was 21,413.13 ± 17,861.00 CFU/ml. High-throughput sequencing revealed 10 bacterial phyla, including 9 identified and 1 unclassified phyla. Totally 63 sequences were identified at the genus level, including 42 genera, 3 tentative species and 18 unclassified genera. In addition, 7 potential human pathogenic bacteria were detected. In summary, department, brand and service life of DCUs do not influence the water quality of DUWLs significantly. The diversity of microbial communities in DUWLs is abundant and includes both pathogenic and some unknown bacteria. Keywords: Water quality, Dental unit waterlines (DUWLs), Microbial contamination, Illumina MiSeq sequencing, Diversity of microbial communities